Analisis Komparatif Kinerja Algoritma Support Vector Machine, Random Forest, dan Naive Bayes untuk Klasifikasi Sentimen pada Komentar YouTube - Eustachius Dito Dewantoro; Sindhu Rakasiwi (Forum Kerjasama Pendidikan Tinggi, 2026)
The rise of social media platforms like YouTube has made them a primary medium for public discourse on socio-political issues, such as the